Perceptions of persons who wear face coverings are modulated by the perceivers’ attitude - Leder, Johannes; Koßmann, Lisa; Carbon, Claus-Christian (Frontiers in Neuroscience, 2022)
Abstract We examined the effect facial covering has on person perception depending on perceivers' attitudes. We used two online experiments in which participants saw the same human targets repeatedly appearing with and without a specific piece of clothing and had to judge the targets’ character. In Experiment 1 (N =101), we investigated how the wearing of a facial mask influences person perception depending on the perceiver’s attitude towards measures against the COVID-19 pandemic. In Experiment 2 (N =114), we examined the effect of wearing a head cover associated with Arabic culture on person perception depending on the perceiver’s attitude towards Islam. Both studies were preregistered; both found evidence that person perception is a process shaped by the personal attitudes of the perceiver as well as the mere targets’ outward appearance. Integrating previous findings, we demonstrate those facial covers, as well as head covers, operate as cues used by the perceivers to infer the targets’ underlying attitudes. The judgment of the target is shaped by the perceived attitude toward what the facial covering stereotypically symbolizes.